Political viewpoints of Abdulla pashew's poem - Partiman Hekmat Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Political viewpoints of Abdulla pashew's poem ) this is the title of the research that tries to describe the connection between literature and politics and its influences on pashew's poem before and after uprising. In this perspective, it studies those reflections in this research exept acknowledgment and the result . This research includes two basic parts,The first part includes; (pashew's view points before uprising) ,and this part is devided into some points like ( pashew's support to oppressed people, pashew as a politicians(pashew in political clothing), pashew and Anflal and anflal's effects on kurds, pashewand standing against Arabization(TA'Arib ), and policies of Iraq government and dialogue with enimes. Part two Incudes pashew's political views after Uprising, and it is devided into two points; (Pashew and critisizm at political parts , pashew and wellcoming honesty , dream of indipendence , and pashew and profanity ) The main point that